Conflict Between Thai Muslims and Thai State in Southern Thailand : Historical Perspectives - Chumphon Kaewsom; Seniwati Ismail; Shamsuddin L. Taya; Ahmad Bashawir Abdul Ghani (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
In the southern border provinces of Thailand, especially Pattani, Yala and Narathiwat, there are two religious group of people, Thai Muslims and Buddhists. They live together, the state and Thai Muslims for a long time. The lack of knowledge in relation to understanding Muslims traditionally religious way of life, Muslims were forced directly or indirectly to act as Thai Buddhists by Thai government. This is one of the biggest conundrum Thai government should address and find an amicable solution urgently. Additionally, it is essential to be noted that historical perspectives of Pattani state is completely different from both side, this can lead to potentially political conflict in this area. Therefore, the government should rewrite a new paradigm by cooperating with all groups of people involve this conflict. If the majority of people could accept the recognition of difference, eventually this will result in peaceful coexistence.